Do "speed bumps" prevent accidents in financial markets? - Jorge Gonçalves; Roman Kräussl; Vladimir Levin (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
Is it true that speed bumps level the playing field, make financial markets more stable and reduce negative externalities of high-frequency trading (HFT) firms? We examine how the implementation of a particular speed bump - Midpoint Extended Life order (M-ELO) on Nasdaq impacted financial markets stability in terms of occurrences of mini-flash crashes in individual securities. We use high-frequency order book message data around the implementation date and apply difference-in-differences analysis to estimate the average treatment effect of the speed bump on market stability and liquidity provision. The results suggest that the introduction of the M-ELO decreases the average number of crashes on Nasdaq compared to other exchanges by 4.7%. Liquidity provision by HFT firms also improves. These findings imply that technology-based solutions by exchanges are feasible alternatives to regulatory intervention towards safer markets.
urn:nbn:de:hebis:30:3-515971
Keywords: C21; G14; G18; 330; mini-flash crash; speed bump; midpoint extended life order